Queering classrooms : personal narratives and educational practice to support LGBTQ youth in schools - Mikulec, Erin A.; Miller, Paul Chamness (Emerald Publishing Limited : Information Age Publishing, Inc., 2016)
Teacher Education programs have largely ignored the needs of LGBTIQ learners in their preparation of pre-service teachers. At best in most of such programs, their needs are addressed in a single chapter in a book or as the topic of discussion in a single class discussion. However, is this minimal discussion enough? What kind of impact does this approach have on future teachers and their future learners?This book engages the reader in a dialogue about why teacher education must address LGBTIQ issues more openly and why teacher education programs should revise their curriculum to more fully integrate the needs of LGBTIQ learners throughout their curriculum, rather than treat such issues as a single, isolated topic in an insignificant manner. Through personal narratives, research, and conceptual chapters, this volume also examines the different ways in which queer youth are present or invisible in schools, the struggles they face, and how teachers can be better prepared to reach them as they should any student, and to make them more visible. The authors of this volume provide insight into the needs of future teachers with the aim of bringing about change in how teacher education programs address LGBTIQ needs to better equipped those entering the field of teaching.
Keywords: Homosexuality and education.; Sexual minorities -- Education.; Sexual minorities -- Identity.; Teachers -- Training of.; Education -- Inclusive Education.; Educational strategies and policy: inclusion.; elektronické knihy; electronic books